RELATIONSHIP BETWEEN BILINGUAL INSTRUCTION AND LEARNERS’ PERFORMANCE IN ENGLISH AS SECOND LANGUAGE CONTEXT - Huma Imran Khan (Journal of Education and Educational Development, 2020)
The prime purpose of this study was to explore a correlationbetween bilingual instruction in an ESL class and the classperformance of the ESL learners at the secondary level. Quantitativeresearch method was used to evaluate the test performance of 60 ESLlearners divided into two groups: One was the controlled group (whichwas given instructions in L2 only) and the other was the treatmentgroup (which was given instructions in both L1 and L2) in PublicSchool settings. Apart from the students, 15 language teachers’ feedbackupon their perceptions of L1 usage in L2 classrooms was takenby using the Likert scale feedback forms. The results confirmed thatthe instructions given bilingually are directly associated to improvedlearner outcomes and teachers’ responses for the usage of L1 inclassrooms showed a strong positive response.
Keywords: bilingual instructions; learner performance; mixed coding; second language